What inclusive instructors do : principles and practices for excellence in college teaching - Addy, Tracie Marcella; Dube, Derek; Mitchell, Khadijah A.; SoRelle, Mallory E. (Stylus Publishing, LLC., 2021)
"This book uniquely offers the distilled wisdom of scores of instructors across ranks, disciplines and institution types, whose contributions are organized into a thematic framework that progressively introduces the reader to the key dispositions, principles and practices for creating the inclusive classroom environments (in person and online) that will help their students succeed"--